Quality Function Deployment (QFD) and the environment. (4th August 2014) - Wong, Hung Kun; Juniper, James
This paper identifies the Quality Function Deployment (QFD) as a tool for 'eco–design' that can be used to identify customer and community needs and requirements and to evaluate and characterise them into different categories, thereby building up an overall picture of customer value. It further argues that QFD can be more effective to the extent that it incorporates green engineering objectives, because it can incorporate sustainable environmental advantages into the existing set of sustainable competitive advantages that have been determined through the conventional QFD implementation process. The paper argues that, in this way, environmental competencies can also emerge as long–term sources of value or uniqueness, and operate as barriers to imitation in guaranteeing sustainable competitive advantage.